Informal learning within the mother-daughter dyad - Yates, Deanne Grier (Kansas State University, 2020)
Formal, non-formal and informal are the accepted descriptions of locations and forms of adult learning. Defining where and recognizing when formal and non-formal learning takes place is uncomplicated and straightforward; formal learning and non-formal learning are planned activities and confined to organized settings. Informal learning is unplanned and occurs in the course of everyday living. The nature of informal learning makes defining where and when it occurs a challenge. Utilizing Marsick and Volpe’s (1999) six characteristics of informal learning, this qualitative study identifies informal learning within the mother-daughter dyad and supports Jarvis’ (2012) theory of learning in the social context. The narratives of the participants lived experiences exhibit the influence of informal learning on the middle-aged daughter’s perception of aging. The effect of informal learning on stereotype formation, moral development, and roles within the family were also established.
Keywords: informal learning; mother-daughter relationship; adult learning; learning in the social context